How Does The Milk Processing Industry in Indonesia Develop Their Technological Capability? - Budi Triyono; Chichi Shintia Laksani; Mohammad Zulhamdani; Saut H Siahaan (STI Policy and Management Journal, 2016)
Increasing public awareness of the importance of milk consumption and the increasing population of Indonesia make milk as an economic commodity that has a strategic value. The purpose of this study are to analyse the technological capabilities dairy processing industry in Indonesia and to understand how the company builds its technological capabilities. This research was conducted through case studies on some of the milk processing companies in Java classified by the ownership of capital are cooperative, local company and foreign company. The results showed differences in technological capabilities. The highest technological capabilities shown by foreign companies and the large-scale local companies. Meanwhile, a technological capability of dairy cooperatives is still low. By categories, mechanisme of technological capability development also different. Technological capabilities in dairy cooperatives conducted through internal efforts that do not involve external parties. Meanwhile, thelarge-scale local companies and foreign companies developed their technology capabilities by involving external partiess such as R & D institutions and foreign parties.